The association of wrist circumference with hypertension in northeastern Chinese residents in comparison with other anthropometric obesity indices - Yongfang Li; Yuyan Liu; Jing He; Ping Ma; Luyang Yu; Guifan Sun (PeerJ, 2019)
Background Wrist circumference (WrC) is an easily obtained measure in estimating the body frame and regional fat distribution, and has increasingly used as an obesity index. The aim of our study is to estimate the association of WrC with elevated blood pressure (BP) among northeastern Chinese community-dwelling residents, and compare the strength of this association to other anthropometric obesity indices. Methods A total of 2,331 adult participants (761 male participants, and 1,570 female participants) were included. WrC and other five generally used obesity indices, including body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR) and neck circumference (NC) were measured. Hypertension was defined as systolic blood pressure (SBP)/diastolic blood pressure (DBP) ≥140/90 mmHg or anti-hypertensive medication use. Multivariable linear and logistic regression models were performed to identify associations of BP and hypertension with per standard deviation (SD) increase of obesity indices. Areas under receiver operative characteristic curves (AUC) were calculated to compare the predicting capacity of WrC and other obesity indices on hypertension. Results All of the six obesity indices were positively associated with both SBP and DBP after adjustment for age and gender (P-values of associations of SBP with obesity indices were 0.043 for WrC, and <0.001 for other five indices; P-values of associations of DBP with obesity indices were 0.011 for WrC, 0.031 for WHR, and <0.001 for other four indices), while the association between SBP and WrC showed no statistically significant after further adjusted for life-style and metabolic risk factors (P-value was 0.062). The increases of both SBP and DBP per SD increase of BMI were the largest. The positive associations of five obesity indices but WHR with hypertension were observed after adjustment for all risk factors (P-values were 0.024 for WrC, 0.064 for WHR and <0.001 for other four indices). However, the odd ratios (OR) of WrC was the smallest, while BMI was the largest. Consistently, the AUC of BMI was the largest and statistically larger than that observed for WrC (P-value <0.001). Conclusions WrC was associated with hypertension among northeastern Chinese populations. However, the association was not stronger than the other generally used indices, particularly BMI.